Perioperative outcomes of thoracoscopic lung resection requiring a long operative time. (12th September 2018) - Mori, Shohei; Noda, Yuki; Tsukamoto, Yo; Shibazaki, Takamasa; Asano, Hisatoshi; Matsudaira, Hideki; Yamashita, Makoto; Odaka, Makoto; Morikawa, Toshiaki
Abstract: OBJECTIVES: Difficult thoracoscopic surgery sometimes requires a long operative time. It is unclear whether patients benefit from such thoracoscopic surgeries. We investigated whether thoracoscopic surgery for difficult cases contributed to improvements in perioperative outcomes. METHODS: We retrospectively reviewed cases of anatomical lung resection with thoracoscopic surgery, including conversion to thoracotomy, between January 2006 and December 2016 and compared patient demographics and perioperative outcomes of the long (≥360 min) and the normal operative time groups (<360 min). RESULTS: One hundred and seventy-six patients were in the long operative time group and 655 patients were in the normal operative time group. The long operative time group had more male patients, more progressive clinical stages, bilobectomy or pneumonectomy, conversion to thoracotomy and more blood loss than the normal operative time group. The long operative time group had higher rates of postoperative complications and longer hospital stay (30% vs 16%, P < 0.001 and 9 ± 9 days vs 7 ± 8 days, P < 0.001; respectively). Multivariate analysis showed that in the first half of the operative period, chronic obstructive pulmonary disease and bilobectomy or pneumonectomy were independent predictive factors for postoperative complications. The long operative time as a factor was close to statistical significance (odds ratio 1.689, P = 0.079) unlike the elective conversion to thoracotomy (odds ratio 0.784, P = 0.667) and emergency conversion to thoracotomy (odds ratio 0.938, P = 0.924). CONCLUSIONS: In conclusion, when difficult cases are encountered, conversion to thoracotomy should be considered by surgeons if continuation of thoracoscopic surgery increases the operative time.